2021
DOI: 10.1007/s11069-021-05056-2
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous regions for rainfall distribution in the city of Rio de Janeiro associated with the risk of natural disasters

Abstract: Understanding the occurrence of natural disasters in regions where the occurrence is high is very important, it is known that the occurrence of disasters associated with intense rains are a source of research in different locations around the globe, being important not only for increasing accuracy of weather forecasting models, but important information for civil defense, where lives can be saved. The increase in the occurrence of natural disasters related to extreme rainfalls has become a problem of large urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The Southeastern region of the country also showed changes in rainfall, with the occurrence of extreme events demonstrated by ; ; Marengo et al (2020) and Zilli et al (2017). For the state of Rio de Janeiro and its capital, changes in rainfall distribution were also identified, along with increase in extreme events related to precipitation, and impacts on population were quantified by Aguiar and Cataldi (2021); Avila et al (2016); Bunhak and Wanderley (2020); Ehrlich et al (2021); Machado et al (2010); Pereira et al (2021). Pristo et al (2018); Silva and Dereczynski (2014); Silva et al (2016) and Wanderley and Bunhak (2016) showed the importance of studying precipitation, its changes and impacts.…”
Section: Introductionmentioning
confidence: 95%
“…The Southeastern region of the country also showed changes in rainfall, with the occurrence of extreme events demonstrated by ; ; Marengo et al (2020) and Zilli et al (2017). For the state of Rio de Janeiro and its capital, changes in rainfall distribution were also identified, along with increase in extreme events related to precipitation, and impacts on population were quantified by Aguiar and Cataldi (2021); Avila et al (2016); Bunhak and Wanderley (2020); Ehrlich et al (2021); Machado et al (2010); Pereira et al (2021). Pristo et al (2018); Silva and Dereczynski (2014); Silva et al (2016) and Wanderley and Bunhak (2016) showed the importance of studying precipitation, its changes and impacts.…”
Section: Introductionmentioning
confidence: 95%
“…According to D 'Orsi et al (2016) approximately 90% of the 50 largest geological-geotechnical accidents recorded in RJC, from 1966 to 2016, took place in Tijuca massif region. According to Pereira et al (2021) the orography of the Tijuca massif is a determining factor for natural disaster related to precipitation in RJC.. The collapse of two buildings in Muzema community was the last major disaster seen in Tijuca massif; it resulted from high rainfall rates recorded in the region in April 2019, which killed 24 citizens.…”
Section: Study Area and Data Sourcesmentioning
confidence: 99%
“…These changes can be associated with anthropic factors such as deforestation, rampant urbanization processes or intensi cation of natural phenomena (Salviano et al 2016, Wanderley and Miguel 2019, Pereira et al 2021. Historical accounts about RJC are often intermingled with the history of inundations and oods in the city since the 16th century.…”
Section: Introductionmentioning
confidence: 99%
“…social and political activities that ensure the stable functioning and sustainable development of the country occur in these urban areas. 11 The importance of investigating how closer collaboration can be established between the DRR profession and urban planners seems to be a step in the right direction of planning for resilient cities.…”
Section: Introductionmentioning
confidence: 99%